2018
DOI: 10.1016/j.ajpath.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Variation in Acute Ischemic Muscle Injury

Abstract: Limited efficacy of clinical interventions for peripheral arterial disease necessitates a better understanding of the environmental and genetic determinants of tissue pathology. Existing research has largely ignored the early skeletal muscle injury response during hind limb ischemia (HLI). We compared the hind limb muscle response, after 6 hours of ischemia, in two mouse strains that differ dramatically in their postischemic extended recovery: C57BL/6J and BALB/cJ. Perfusion, measured by laser Doppler and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Previous reports have indicated that dystrophin IF staining is rapidly reduced in skeletal and cardiac muscle during early myonecrosis(19,32). Immunofluorescent staining for the sarcolemmal protein dystrophin and the extracellular matrix protein laminin was performed on a subset of transverse sectioned muscles to assess the possibility that muscles were incurring damage during the contraction protocols.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous reports have indicated that dystrophin IF staining is rapidly reduced in skeletal and cardiac muscle during early myonecrosis(19,32). Immunofluorescent staining for the sarcolemmal protein dystrophin and the extracellular matrix protein laminin was performed on a subset of transverse sectioned muscles to assess the possibility that muscles were incurring damage during the contraction protocols.…”
Section: Resultsmentioning
confidence: 94%
“…The muscles were then equilibrated for 10 mins, followed by stimulated isokinetic contractions every 10 mins for 180 mins (18 total contractions). We chose this timing based on our previous observation that excitation contraction coupling is impaired in muscles isolated from BALB/c mice 180 minutes after induction of acute hindlimb ischemia (in the absence of histological signs of tissue necrosis)(19). A second force frequency curve was measured following the 180-min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, using an in vivo mouse hindlimb ischemia model (without reperfusion), we found that myonecrosis develops between three and six hours after the onset of ischemia and is accompanied by a complete loss of contractile function [19]. This led us to examine the <3-hour time domain in this study to better define the timing of muscle functional impairments and associated terminal metabolite changes that occur during acute hypoxia.…”
Section: Introductionmentioning
confidence: 98%
“…Our data provide a novel characterization of hypoxic muscle mechanical/energetic failure and paint a detailed picture of the timing of these impairments. This information can be used in conjunction with existing in vivo rodent hindlimb ischemia/reperfusion studies [5,16,17,19] to generate new hypotheses regarding optimal timing of reperfusion or administration of precision therapeutics.…”
Section: Introductionmentioning
confidence: 99%